Asymptotic stability of a repairable system with imperfect switching mechanism - Houbao Xu; Weihua Guo; Jingyuan Yu; Guangtian Zhu (International Journal of Mathematics and Mathematical Sciences)
This paper studies the asymptotic stability of a repairable system with repair time of failed system that follows arbitrary distribution. We show that the system operator generates a positive C0-semigroup of contraction in a Banach space, therefore there exists a unique, nonnegative, and time-dependant solution. By analyzing the spectrum of system operator, we deduce that all spectra lie in the left half-plane and 0 is the unique spectral point on imaginary axis. As a result, the time-dependant solution converges to the eigenvector of system operator corresponding to eigenvalue 0.